The relationship of organizational citizenship behaviour with adaptive work performance among Kolej Universiti Islam Melaka's staff - Omar Mokhtar, Muhammad Yasin; Puteh, Baharudin; Norman, Hamidah; Ab Rahman, Suzana; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2021)
The workplace is becoming increasingly dynamic, and employees have to manage uncertain and unpredictable work situations during these pandemic seasons. Therefore, the top management must strive to update the rules and administrative procedures in order to create a good working situation so that the employees’ performance is always at the best level. The purpose of the study is to identify the relationship between organizational citizenship behaviours (OCB) with Adaptive Work Performance among academic and non -academic staff. This study consisted a total of 77 respondents from academic and non-academic staff of Kolej Universiti Islam Melaka. The sampling method used by the researcher is purposive sampling where the sample consists of a specific sample and coincides with the objectives of the study. The findings show that there is a significant positive relationship between Organizational Citizenship Behaviour with adaptive work performance. The implications of future studies suggest the importance of job satisfaction, organizational commitment and organizational citizenship behaviours in influencing organizational effectiveness and performance.